(untitled) (Architecture Image Studies, 2026)
The impact of economic growth on environmental quality remains uncertain, with inconsistent results across various indicators. This study aims to address this gap by examining the effects of economic growth, gasoline consumption, and population on air quality in developing countries. The Environmental Kuznets Curve (EKC) theory suggests an inverted U-shaped relationship between economic growth and environmental degradation, but empirical evidence, especially in developing countries, remains mixed. Using panel data analysis, this study combines these three variables to provide a more comprehensive understanding of their collective impact on air quality. Data from 24 developing countries from 2014 to 2023 are analyzed, with findings revealing significant influences of economic growth, gasoline consumption, and population dynamics on air quality. Based on these findings, a key policy implication is enhancing public awareness of ecological issues to encourage environmental responsibility. Educating the public on the impact of their actions can promote sustainable practices, such as reducing energy use and waste. Additionally, promoting sustainable economic development models is essential. Developing countries should focus on balancing growth with environmental protection by adopting green technologies, renewable energy, and environmentally conscious industrial practices. This research contributes to the understanding of how economic and demographic factors interact to affect air quality in developing nations.